Change Mechanisms in Patient-Preferred Live Music: An Exploratory Interpretivist Study. (10th May 2021) - Silverman, Michael J
Abstract: Although there is empirical support for patient-preferred live music (PPLM) in addressing affective states and pain for adults in medical settings, there is a lack of data regarding why PPLM might be effective. Identifying the underlying processes and events of change mechanisms within PPLM has the potential to improve education and clinical training, distinguish music therapy from other music interventions, and augment treatment outcomes for service users. The practitioner's expertise constitutes a component of evidence-based practice and could be used to identify change mechanisms that result in PPLM being effective. Therefore, the purpose of this exploratory interpretivist study was to understand practitioners' perceptions of PPLM change mechanisms for adults in medical settings. I conducted in-depth individual semi-structured interviews with 10 practitioners who had provided protocol-based PPLM in adult medical settings as a component of published research projects. Incorporating member checking and trustworthiness, I used an inductive approach to thematic analysis to analyze data. I identified 3 major themes: Choices within PPLM, Music-based aspects of PPLM, and Positive outcomes resultant of PPLM. These themes were supported by 17 subthemes. The subthemes helped to explain relationships between results and I developed a visual model to conceptualize PPLM change mechanisms. While previous objectivist literature has found PPLM to be an effective intervention for adults in medical settings, the results of the current study provide an evidence-based and practitioner-centric approach to PPLM change mechanisms. Implications for clinical practice, limitations of the study, and suggestions for future research are provided.